Association between parent-proxy-reported and child-self-reported perceptions of children’s motor competence and children’s performance-based motor skill abilities - Alice Humble; Mon-Lin Yu; Ted Brown (Scandinavian Journal of Occupational Therapy)
Background When assessing motor skills, occupational therapists are encouraged to seek the perspectives of children and their parents to promote the delivery of client-centered care.Aim To investigate whether 9–12-year-old children’s views and their parents’ proxy views of the children’s motor skill competence and their performance on a standardized, performance-based assessment are associated.Materials and methods Thirty 9–12-year-old children completed the Perceived Motor Competence Questionnaire in Childhood (PMC-C) and the Pictorial Scale of Perceived Movement Skill Competence – version 2 (PMSC-2), while their parents completed the Movement Assessment Battery for Children–2nd Edition Checklist (MABC-2 Checklist). Children’s objective motor skills were measured by the Bruininks-Oseretsky Test of Motor Proficiency–2nd Edition (BOT-2). Spearman’s rho correlations were used to analyze the data.Results Significant associations were found between the BOT-2 total motor composite and the PMC-C. A significant association was found between the MABC-2 Checklist and the BOT-2 Strength and Agility composite, as well as the PMC-C total score.Significance and conclusions Occupational therapists are encouraged to include children and their parents in the therapeutic process to capture individual perspectives and deliver client-centered care.